Oxygen-sensitive nanoparticles reveal the spatiotemporal dynamics of oxygen reduction during magnesium implant biodegradation - Berit Zeller-Plumhoff; Ashwini Rahul Akkineni; Heike Helmholz; Dmytro Orlov; Maria Mosshammer; Michael Kühl; Regine Willumeit-Römer; Michael Gelinsky (npj Materials Degradation, 2022)
Abstract Magnesium (Mg) alloys are becoming increasingly important in the biomedical field as temporary bone implants. However, the biodegradation process of Mg alloys is highly complex and recent findings suggest that oxygen (O2) consumption is non-negligible. In this study, we give experimental proof of O2 consumption during Mg degradation under physiological conditions. Specifically, we study pure Mg, Mg–6 wt%Ag and Mg–5 wt%Gd in Hanks’ balanced salt solution and Dulbecco’s modified Eagle’s medium. We show that O2 consumption and hydrogen evolution are inversely correlated and that O2 concentrations remain below 7.5% in certain cases, which could have significant implications for bone healing.